Analysis of Housing Settlement Patterns on the Banks of the Chilca River - Ramirez Pihui, Eliane Estefany (2024)
According to the Peruvian Chamber of Construction, 80% of the houses are informal constructions built with cheap materials and located in risk areas such as riverbanks, endangering the physical integrity of their occupants due to the constant erosion of the material subject to possible damage over time. This work develops the analysis of the settlement patterns of dwellings on the banks of the Chilca River. For the work, 265 houses were analyzed by the method of visual observation based on a card, and the sample was reduced to 234 houses due to the lack of access at some points, including 120 houses from Real Avenue to Jose Olaya Avenue, 58 houses from Jose Olaya Avenue to Inclan Street, and 56 houses from Inclan Street to the intersection of ocopilla, which was obtained in the field by the authors. Finally, 3 characteristic patterns were observed in the GBP (49.14%), PV (33.77%) and HRP (17.09%) dwellings, with the GBP-2 typology representing 25.64% of the dwellings, while the RP-1 represented 24.36%. The settlement patterns have a distribution in the territory that is associated by blocks. For example, in sectors 1 and 3, there is a greater presence of RP, while in sector 2 HRP predominates, and the presence of GBP is distributed in the 3 sectors analyzed.